Position Paper – Building a New Life in Australia: The Longitudinal Survey of Humanitarian Migrants - Department of Immigration and Citizenship (My University, 2012)
The paper discusses the key design choices, and the strengths and weaknesses of different design options for ‘Building a New Life in Australia: The Longitudinal Study of Humanitarian Migrants’. It also outlines a suggested design and architecture for the study.
Keywords: Culture -- Immigrants; Life Events -- Immigration / newly arrived migrants; Disadvantage, adversity and resilience; Life Events; Culture; Immigration / newly arrived migrants; Immigrants; Adversity and resilience; Dsiadvantage, adversity and resilience